Partisipasi Masyarakat Terhadap Pengelolaan Hutan Lindung Mangrove Di Desa Sarawet Kecamatan Likupang Timur Kabupaten Minahasa Utara - Fransisco Daniel Sinaga; Melsje Yellie Memah; Jean Fany Junita Timban (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the level of community participation and to analyze the relationship between internal and external factors with the level of community participation in the management of mangrove protected forests in Sarawet Village, Likupang Timur District, North Minahasa Regency. This research was conducted from December 2021 to February 2022. The selection of respondents was carried out by accidental sampling. The data used are primary data and secondary data. Primary data were collected through questionnaire-based interviews with 76 people. Secondary data was obtained from related agencies, namely the Old Law Office of Sarawet Village, North Minahasa Regency. Secondary data was also obtained through the internet using Google Scholar in the form of books, journal articles and theses related to the topic of this research, namely Community Participation in Mangrove Protected Forest Management. The results showed that the level of community participation in Sarawet Village, East Likupang District in the planning, implementation, utilization and evaluation stages was low and the relationship between internal and external factors on community participation as a whole had a significant relationship with a sig value of 0.000 < 0.01.